Towards understanding the biological function of the unusual chaperonin Cpn60.1 (GroEL1) of Mycobacterium tuberculosis. (March 2016) - Sharma, Aditi; Rustad, Tige; Mahajan, Gaurang; Kumar, Arun; Rao, Kanury V.S.; Banerjee, Sharmistha; Sherman, David R.; Mande, Shekhar C.
Summary: The 60 kDa heat shock proteins, also known as Cpn60s (GroELs) are components of the essential protein folding machinery of the cell, but are also dominant antigens in many infectious diseases. Although generally essential for cellular survival, in some organisms such as Mycobacterium tuberculosis, one or more paralogous Cpn60s are known to be dispensable. In M. tuberculosis, Cpn60.2 (GroEL2) is essential for cell survival, but the biological role of the non-essential Cpn60.1 (GroEL1) is still elusive. To understand the relevance of Cpn60.1 (GroEL1) in M. tuberculosis physiology, detailed transcriptomic analyses for the wild type H37Rv and cpn60.1 knockout ( groEL1-KO ) were performed under in vitro stress conditions: stationary phase, cold shock, low aeration, mild cold shock and low pH. Additionally, the survival of the groEL1-KO was assessed in macrophages at multiplicity of infection (MOI) of 1:1 and 1:5. We observed that survival under low aeration was significantly compromised in the groEL1-KO . Further, the gene expression analyses under low aeration showed change in expression of several key virulence factors like two component system PhoP/R and MprA/B, sigma factors SigM and C and adversely affected known hypoxia response regulators Rv0081, Rv0023 and DosR. Our work is therefore suggestive of an important role of Cpn60.1 (GroEL1) for survival under low aeration by affecting the expression of genes known for hypoxia response.